PENGARUH CEO DUALITY - Kevin Chandra; Devie Deviesa (Business Accounting Review, 2017)
This Study Aimed to examine and to prove the reciprocal relationship between CEO Duality and Firm Value which is measured with Tobin’s Q ratio and with Earning Management as an intervening variable. This study was conducted on public companies in Indonesia which are also listed in LQ45 categories in 2012-2015 in consecutive. And with total sample of 52 will be processed using smartPLS software. The result showed that there is a positively significant relationship between CEO Duality and Firm Value. And negatively significant relationship between the intervening variable CEO Duality to Earning Management, and Earning Management to Firm Value.